2005
DOI: 10.1002/jsfa.2386
|View full text |Cite
|
Sign up to set email alerts
|

Determination of volatile compounds to characterize fish spoilage using headspace/mass spectrometry and solid‐phase microextraction/gas chromatography/mass spectrometry

Abstract: Changes in volatile compounds were monitored in whiting (Merlangius merlangus), cod (Gadus morhua) and mackerel (Scomber scombrus) and related to spoilage. Data are presented from headspace/mass spectrometric (HS/MS) analysis and solid-phase microextraction/gas chromatographic/mass spectrometric (SPME/GC/MS) analysis at two time points (day 0 and day 10) during storage at 4 • C. HS/MS revealed 24 ions that could be used as markers of spoilage. SPME/GC/MS identified 86 compounds, 20 of which could perhaps be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 39 publications
11
110
1
Order By: Relevance
“…The level of 1-octen-3-ol, which produces a characteristic off flavor upon oxidation by lipoxygenase, decreased from 6.07% to 4.65%. It was reported that short-chain volatile carbonyls and unsaturated alcohols can be formed from the oxidization of PUFAs by lipoxygenase (Duflos et al, 2006). Alkanes in the TP-treated hydrolysate increased from 13.29% to 27.45%; in particular, n-hexane increased by 208.31%, and n-heptane increased by 101.80%.…”
Section: Spme-gc-ms Analysismentioning
confidence: 96%
See 3 more Smart Citations
“…The level of 1-octen-3-ol, which produces a characteristic off flavor upon oxidation by lipoxygenase, decreased from 6.07% to 4.65%. It was reported that short-chain volatile carbonyls and unsaturated alcohols can be formed from the oxidization of PUFAs by lipoxygenase (Duflos et al, 2006). Alkanes in the TP-treated hydrolysate increased from 13.29% to 27.45%; in particular, n-hexane increased by 208.31%, and n-heptane increased by 101.80%.…”
Section: Spme-gc-ms Analysismentioning
confidence: 96%
“…Among the aldehydes, 2,4-heptadienal and (Chung et al, 2001;Chung et al, 2002;Lin et al, 2014) Note: '--' indicates that the corresponding compound was not detected. 2,4-decadienal, which are formed from the autoxidation of unsaturated fatty acids, have been identified as common odor compounds in aquatic products (Duflos, et al, 2006;Iglesias and Medina, 2008). Moreover, saturated aldehydes, such as n-pentanal, n-heptanal and n-octanal, have been identified as the primary contributor to the lipase taste, and n-hexanal has been associated with the characteristic flavor and odor that are described as rancid and grassy (Duflos et al, 2006;Iglesias and Medina, 2008;Shi et al, 2009).…”
Section: Spme-gc-ms Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[90][91][92] In search of further spoilage markers, Duflos et al identified 20 common volatiles from whiting, mackerel, and cod. 90 For these substances, the contribution to the entire smell of the fish is partially known. 93 It was shown that the characteristic spoilage compounds fluctuate significantly from one species to another.…”
Section: Food and Beveragementioning
confidence: 99%